ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN SYARIAH KARYAWAN BANK SYARIAH DI KABUPATEN KARIMUN - Nasrullah, Muhammad; Koesmawan (An Nuqud Journal of Islamic Economics, 2025)
This research aims to analyze the factors influencing the level of Islamic financial literacy among employees of Bank Riau Kepri Syariah in Karimun Regency, Riau Islands Province. The study employs a descriptive quantitative approach with factor analysis techniques. The population in this study consists of all employees of Bank Riau Kepri Syariah Branch Tanjung Balai Karimun, totaling 64 individuals, who were also used as respondents (total sampling). Data collection was carried out through the distribution of questionnaires, while data processing and analysis were conducted with the assistance of SPSS software version 25.0. The research results indicate that the level of financial literacy among employees is categorized as low literate, with a percentage of 30.23%. Out of the nine factors tested, only one factor was found to have a significant influence on the level of financial literacy in Islamic finance, namely the perception of Islamic banking products. Meanwhile, the other eight factors did not show a significant influence either partially or simultaneously on the level of financial literacy in Islamic finance. The conclusion of this research indicates that although employees work in an Islamic banking environment, their understanding of the principles and products of Islamic finance remains relatively low. Therefore, it is necessary to enhance the capacity of human resources through ongoing training and comprehensive internal literacy programs in order to optimally improve the quality of Islamic financial services